2019
DOI: 10.1080/10400435.2019.1601649
|View full text |Cite
|
Sign up to set email alerts
|

Assistive robotic arm: Evaluation of the performance of intelligent algorithms

Abstract: Assistive robotic devices can be used to help people with upper body disabilities gaining more autonomy in their daily life. Although basic motions such as positioning and orienting an assistive robot gripper in space allow performance of many tasks, it might be time consuming and tedious to perform more complex tasks. To overcome these difficulties, improvements can be implemented at different levels, such as mechanical design, control interfaces and intelligent control algorithms. In order to guide the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…This suggest that the selection and use of appropriate material that will enhance comfort should attract adequate attention. This is supported by the findings of Lebrasseur et al (2019) that the ability and possibility of performing daily activities with ease will reduce stress and possibly elongate life span especially if achieved within the living spaces. Folorunso and Ahmad (2013) observed that several finishing materials are in use in Nigeria.…”
Section: Introductionmentioning
confidence: 67%
“…This suggest that the selection and use of appropriate material that will enhance comfort should attract adequate attention. This is supported by the findings of Lebrasseur et al (2019) that the ability and possibility of performing daily activities with ease will reduce stress and possibly elongate life span especially if achieved within the living spaces. Folorunso and Ahmad (2013) observed that several finishing materials are in use in Nigeria.…”
Section: Introductionmentioning
confidence: 67%
“…It is controlled with a 7 degrees of freedom (DoF) Cartesian algorithm (three translations, three rotations, and hand opening/closing). Recently, specialized control modes (e.g., drinking mode, preset positions, and trajectories) were integrated to improve usability of JACO during more complex tasks 40,41 . It can be integrated with various powered wheelchair control interfaces, completed by switch buttons to select control modes (wheelchair vs. JACO, JACO's DoF, specialized modes).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, specialized control modes (e.g., drinking mode, preset positions, and trajectories) were integrated to improve usability of JACO during more complex tasks. 40,41 It can be integrated with various powered wheelchair control interfaces, completed by switch buttons to select control modes (wheelchair vs. JACO, JACO's DoF, specialized modes). For all participants in the study, JACO was integrated with the users' 2 DoF wheelchair joystick.…”
Section: Jaco Robotic Armmentioning
confidence: 99%
“…In any case, a common way to deal with the interface's lower dimensionality is often to arrange the AT's modes in sub-control groups. As shown in Figure 1, with this approach, accessing a mode can require a series of actions to browse through the nested groups [1,15,16]. Thus, a strategy needs to be implemented within the interface to either reduce the total number of modes, facilitate switching between them, or somehow artificially augment the dimensionality of the interface itself.…”
Section: Introductionmentioning
confidence: 99%
“…At each level, the modes are proposed to the user, one-by-one, and the user activates the switch when the mode they want is proposed. Although this strategy is quite robust (due to its simplicity) and, thus, commonly found in practice [19], it is time consuming and does not lead to a satisfactory user experience [15].…”
Section: Introductionmentioning
confidence: 99%